Математична модель для оптимізації спільної вакцинації та антивірусної терапії - Ханін, Г. С. (ХНУРЕ, 2023)
The object of research is a mathematical model for the optimization of general vaccination and antiviral therapy. Human influenza is a contagious disease which if proper precautions are not taken to control the disease can lead to massive mortality rates and high costs will be incurred to control the disease in case of an outbreak. As a result, we investigate how the cost of implementing both vaccination and antiviral therapy can be minimized and at the same time minimize the number of infected individuals.
Keywords: спільна вакцинація; антивірусна терапія; метод максимальної ентропії